The development of a memory-system for the second generation SUNSAT micro-satellite - Badenhorst, P. J.(Petrus Johannes),1972- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1997.